The nutrient footprint of a submerged‐cage offshore aquaculture facility located in the tropical Caribbean. Issue 2 (21st February 2019) - Welch, Aaron W.; Knapp, Angela N.; El Tourky, Sharein; Daughtery, Zachary; Hitchcock, Gary; Benetti, Daniel
Abstract : The effect of effluent generated by a commercially scaled offshore (~13 km) finfish aquaculture facility in the tropical Caribbean on the water column and benthic nutrients and chlorophyll‐ a is described. Water column samples were collected up‐ and downstream of the site at various times between 2012 and 2018. Typically, no significant difference in dissolved oxygen, chlorophyll‐ a, particulate organic carbon, particulate organic nitrogen, nitrate + nitrite, and total dissolved nitrogen concentration was observed in the water column between the up‐ versus downstream samples. Similarly, sediment samples were collected at various times between 2012 and 2018. Samples were collected at up‐ versus downstream locations and analyzed for benthic carbon, nitrogen, and chlorophyll‐ a content. Some of the collected data demonstrates a trend toward sediment enrichment within the vicinity of the farm. These data are of interest to stakeholders concerned with the expansion of offshore aquaculture in the United States and other countries. To our knowledge, this is the first report of its kind from a commercially scaled aquaculture facility utilizing offshore submersible‐cage technologies.